"LINGUISTIC FEATURES OF ADVERTISING SLOGANS OF SOFT DRINKS IN ENGLISH AND VIETNAMESE" - Đặng Trần Hoài Dương (2015)
Introduction; Literature review and theoretical background; Research design and methodology; ...